Study of Building Mass Forms in Jardin Cihampelas Apartment - Andiyan Andiyan; Wima Alkad Albadira (Prodi Arsitektur Universitas Matana, 2021)
Cihampelas Street Bandung is one of the main tourist destinations in Bandung; besides that, Cihampelas is also a residential area with a high population density. Jalan Cihampelas has many residential places, one of which is the Jardin Cihampelas Apartment. The Jardin Cihampelas Apartment is a building consisting of 4 building towers, namely towers A, B, C, and D. Each tower has 23 floors, and a U shape, Tower A - B and C - D are located close to each other on the inside of the